HUBUNGAN LINGKAR PINGGANG DENGAN KEJADIAN DIABETES MELLITUS PADA PASIEN USIA 30 SAMPAI 50 TAHUN DI PUSKESMAS KOTA MATSUM MEDAN - Dian Afriandi (Jurnal Penelitian Kesmasy, 2019)
The purpose of this study was to identify blood sugar levels in obese patients in the Matsum City Public Health Center Medan and to analyze the relationship between waist circumference and the incidence of type 2 diabetes mellitus in patients at the Matsum City Public Health Center in Medan. This research was conducted by analytic survey with a Cross Sectional design where all data concerning research variables were collected by approaching, observing or collecting data at a time. The sample used was 69 people. The results in this study found that there was a relationship between waist circumference and the incidence of diabetes mellitus in patients in the Work Area of Kota Matsum Health Center, Medan, North Sumatra.